COVID-19 in periodontal patients - Perszke, Michał; Egierska, Dominika (Journal of Education, Health and Sport, 2022)
Periodontitis is a complex multifactorial disease. COVID-19 pandemic prompted researchers to look for a relationship between SARS-CoV 2 infection and periodontal diseases. The SARS-CoV 2 pathomechanism is associated with the ACE2 receptor, which is highly expressed in periodontal patients. The virus causes a cytokine storm which is also seen in periodontitis. Periopathogen proteases can degrade the S protein of the virus, which facilitates its entry into the host cell. In addition, galectin-3, a protein present in periodontitis, is morphologically similar to the S protein of the virus, which may cause the easier attachment of the virus with the host cell more easily and increase the immune response. In patients infected with SARS-CoV 2, oral lesions such as erosions, ulcers, petechiae, acute parotitis and necrotizing gingivitis occur. The aim of the study is to present the latest reports on the possible mechanisms of the influence of periodontal diseases on the infection and course of SARS-CoV 2 infection and to describe cases of changes in the oral cavity in the course of COVID-19.